Evaluation of supramolecular complex of fenbendazole effect on embryonic development - A. I. Varlamova (Российский паразитологический журнал, 2022)
The purpose of the research is to study the embryotropic effect of supramolecular complex of fenbendazole (SMСF).Materials and methods. The experiment to assess the embryotropic properties of SMCF was carried out on 40 white female and 20 male rats in accordance with the Guidelines for the experimental (preclinical) study of new pharmacological substances. Pregnant female rats were divided into 3 experimental and one control groups. SMCF was administered intragastrically on the 1–6 days of embryogenesis (group 1); on the 7–14 days (group 2) and on the 15–19 days (group 3) in three times therapeutic dose – 6,0 mg/kg of active substance. The animals of the control group received saline from the first to the 19th days of pregnancy. Rats were euthanized on the 20th day of pregnancy. The uterus with fetuses was removed after laparotomy, the number of corpora lutea, implantation sites, the number of living, dead and resorbed fetuses were recorded, the weight and diameter of the placenta were determined. The embryos were examined, weighed, the craniocaudal sizes were determined, the levels of total embryonic, preimplantation and postimplantation embryo death were calculated. The fetuses were examined for abnormalities of internal organs and changes in the skeletal system according to the methods of J. G. Wilson (1965) and A. B. Dawson (1926), modified in the department of embryology of the IEM of the USSR Academy of Medical Sciences.Results and discussion. As a result, SMCF does not induce toxic effects on the fetus: mortality rates, size and weight of embryos were at the level of the control group in a threefold therapeutic dose 6,0 mg/kg at intragastric administration on the 1–6; 7–14 and 15–19 days of pregnancy. SMCF did not cause external and internal malformations.